(untitled) - Messonnier, Shawn (St. Louis, 1997)
Presents discussions on ways to market services offered by veterinary practices, in an effort to increase practice income. Includes a new compilation of money-marketing tips for veterinary practitioners
Keywords: Veterinary medicine; Practice